2011
DOI: 10.1128/jvi.02561-10
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Human Papillomavirus Type 38 E7 Regulates Actin Cytoskeleton Structure for Increasing Cell Proliferation through CK2 and the Eukaryotic Elongation Factor 1A

Abstract: We previously reported that the oncoproteins E6 and E7 from cutaneous human papillomavirus type 38 (HPV38) can immortalize primary human keratinocytes in vitro and sensitize transgenic mice to develop skin cancer in vivo. Immunofluorescence staining revealed that human keratinocytes immortalized by HPV38 E6 and E7 display fewer actin stress fibers than do control primary keratinocyte cells, raising the possibility of a role of the viral oncoproteins in the remodeling of the actin cytoskeleton. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 63 publications
3
24
0
Order By: Relevance
“…Therefore, we compared the status of stress fibers in cells expressing HPV16 E7 to those of control, GFP-expressing cells and cell expressing dominant negative p190 (p190RA). For the purposes of these functional assays, we utilized human osteosarcoma U2OS cells, since they were previously utilized for similar assays and were shown to behave similarly to human keratinocytes in these experiments (47). In addition, we also confirmed the results of these assays in human keratinocyte HaCat cells.…”
Section: Figsupporting
confidence: 56%
See 1 more Smart Citation
“…Therefore, we compared the status of stress fibers in cells expressing HPV16 E7 to those of control, GFP-expressing cells and cell expressing dominant negative p190 (p190RA). For the purposes of these functional assays, we utilized human osteosarcoma U2OS cells, since they were previously utilized for similar assays and were shown to behave similarly to human keratinocytes in these experiments (47). In addition, we also confirmed the results of these assays in human keratinocyte HaCat cells.…”
Section: Figsupporting
confidence: 56%
“…The HPV16 E7 reduction in RhoA-GTP was shown to be due in part to E7 modulation of the cytoplasmic localization of p27, which can in turn bind and dysregulate RhoA (46). On the other hand, HPV38 E7 uses two distinct mechanisms to downregulate Rho activity: (i) mediating the activation of the CK2-MEK-extracellular signalregulated kinase (ERK) pathway and (ii) directly binding to eukaryotic elongation factor 1A (eEF1A) and abolishing its effects on actin fiber formation (47). Due in part to these published observations and considering that p190 is a direct regulator of the Rho pathway, we wanted to assess the biological consequences of E7-p190 interaction.…”
Section: Figmentioning
confidence: 99%
“…In addition, HPV38 E7 is able to induce actin fiber disruption by directly binding to the eukaryotic elongation factor 1A (eEF1A) and abolishing its effects on actin fiber formation. Their data support the conclusion that HPV38 E7 promotes keratinocyte proliferation in part by negatively regulating actin cytoskeleton fiber formation and by binding to eEF1A and inhibiting its effects on actin cytoskeleton remodeling (Yue et al, 2011). Cells from laryngeal papillomas and normal epithelium were cultured in vitro.…”
Section: Fig 1 Schematic Representation Of Monomeric and Filamentousupporting
confidence: 56%
“…HPV proteins are interacted with cell skeletal filaments. Some of these proteins are E6 (HPV16,18), E7 (HPV16,18,38), E5 (high and low risk HPV types), E1^E4 (HPV16), E4 proteins (Lee & Dominguez, 2010;McIntosh et al, 2010;Nguyen 2008;Rey et al, 2000, Safi Oz, 2010Stanley, 2001;Uribe & Jay., 2009;Yue et al, 2011).…”
Section: Wwwintechopencommentioning
confidence: 99%
“…We first used HEK 293T cells to determine which sites in eEF1A1 binding to FAT10. eEF1A1 was divided into various structural domains, C-terminally truncated eEF1A1 mutants and truncated eEF1A1 fragments (24,25). Co-IP experiments indicated that the eEF1A1 region in aa 284-332 and aa 394-462 contains the FAT10 interaction region (Fig.…”
Section: Fat10 Binds To Lysine Residues On Eef1a1 To Influence Its Fumentioning
confidence: 99%